Size-dependent compressive strength properties of hard rocks and rock-like cementitious brittle materials. Issue 4 (4th July 2019) - Darbor, Mohammad; Faramarzi, Lohrasb; Sharifzadeh, Mostafa
Abstract: Rock engineering projects have always been constructed on different (from micro to macro) scales. This makes understanding rock behaviour at different scales essential. In previous statistical studies on igneous hard rocks, the correlation of uniaxial compressive strength (UCS) values in different diameters with estimations of specimen size effect models was weak. In view of this knowledge gap, the present research proposed a model of appropriate size effect in igneous hard rocks. This research also aimed at discussing the effect of specimen size and grain size on the UCS of concrete specimens. To achieve these aims, studies were conducted in parallel on the previous and new experimental data. Non-linear regression analysis on igneous hard rocks indicated that there is a better agreement between the outputs of the multi-fractal scaling model and the specimen size effect model using the fracture energy theory and the results of previous laboratory tests. In addition, in the experimental study, the grain size effect on the predictions of specimen size effect models was exhibited. The results of this research can be used for designing engineering projects at different scales.